Indeks Kekeringan Provinsi Riau Menggunakan Teori Run Berbasis Data Satelit - Sharie, Barcha Yolandha; Fauzi, Manyuk; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Drought disaster is caused by the decreasing of rainfall from normal condition and the duration of dry season. And the effect is show the reducing of water availability. Based on the drought disaster risk index map by National Disaster Management Agency, can be seen that 40-60 % Riau Province got drought. Therefore, it is necessary to anticipate to reduce the impact of drought by calculate the drought index using Run Theory. Drought index can be used to indicate the longest and the greatest number of drought. The rain data who used for the calculation of the drought index is satellite rainfall data in the last 8 years from 2009 to 2016 for every district in Riau Province. The rainfall data is divided into 2 groups, 15 days for daily rainfall data and 30 days for monthly rainfall data. For 15 daily rainfall data, the longest drought duration is 7.5 months and the greatest number of drought is 494.943 mm. While for monthly rainfall data, the longest drought duration is 12 months and the greatest number of drought is 508.6 mm. based on calculation classification level of drought for dryness criteria 15 daily rainfall data from Indragiri Hilir as many as 5 times incident. For monthly rainfall data is Rokan Hilir, Pelalawan, and Kuantan Singingi as many as 3 times incident. Level of drought depiction map using ArcMap 10.1 software.Keywords: Run Theory, drought index, level of drought classification, satellite rainfall data